2021
DOI: 10.1111/acel.13489
|View full text |Cite
|
Sign up to set email alerts
|

Age‐dependent integrity of the meiotic spindle assembly checkpoint in females requires Aurora kinase B

Abstract: A hallmark of advanced maternal age is a significant increase in meiotic chromosome segregation errors, resulting in early miscarriages and congenital disorders. These errors most frequently occur during meiosis I (MI). The spindle assembly checkpoint (SAC) prevents chromosome segregation errors by arresting the cell cycle until proper chromosome alignment is achieved. Unlike in mitosis, the SAC in oocytes is desensitized, allowing chromosome segregation in the presence of improperly aligned chromosomes. Wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 55 publications
1
24
0
Order By: Relevance
“…The SAC is desensitized during oocyte meiosis, permitting chromosomal segregation in the presence of several chromosomal misarrangements [27]. Even though the SAC was induced during meiosis, almost 44% of HtrA2-KD oocytes extruded the rst polar body (Fig.…”
Section: Htra2 Knockdown Causes Cytoskeletal Disorganization In Young...mentioning
confidence: 97%
See 1 more Smart Citation
“…The SAC is desensitized during oocyte meiosis, permitting chromosomal segregation in the presence of several chromosomal misarrangements [27]. Even though the SAC was induced during meiosis, almost 44% of HtrA2-KD oocytes extruded the rst polar body (Fig.…”
Section: Htra2 Knockdown Causes Cytoskeletal Disorganization In Young...mentioning
confidence: 97%
“…Given that decreased HtrA2 expression impeded extrusion of the rst polar body, we hypothesized that HtrA2 might be involved in spindle organization or migration during meiosis. During this process, the SAC acts as a safety mechanism, which holds the oocyte in the metaphase-to-anaphase transition of meiotic phase I until all chromosomes are aligned and microtubules have been correctly attached [27]. Given the arrest in MI of HtrA2-KD young oocytes, we hypothesized potential activation of the SAC.…”
Section: Htra2 Knockdown Activates the Sac In Young Mouse Oocytesmentioning
confidence: 99%
“…The SAC is triggered by unattached kinetochores. In a recent study on mice oocytes, it was revealed that AURKB appears to play a role in the maintenance of the female reproductive lifespan, most likely because of its defensive property against the excessive accumulation of reactive oxygen species in the egg [ 51 ]. However, this is only one possible factor among others.…”
Section: Effect Of Advanced Maternal Age On Chromosomal Segregation A...mentioning
confidence: 99%
“…However, this is only one possible factor among others. Therefore, further investigations on the abundance of AURKB with respect to the advancing age of the egg could shed light on its ability to be used as an adequate biomarker for oocyte developmental competence in women with aging-related decreases in fertility [ 51 ].…”
Section: Effect Of Advanced Maternal Age On Chromosomal Segregation A...mentioning
confidence: 99%
“…AURKC is responsible for most functions that AURKB-CPC has in mitosis [ 8 , 9 ], including regulating chromosome alignment and correcting erroneous kinetochore-microtubule attachments [ 10 12 ]. As a result, AURKB is diffuse in the oocyte cytoplasm and has still to be defined mechanisms in protecting egg quality with age [ 13 , 14 ]. Therefore, subcellular localization and function of AURKA and AURKC in mouse oocytes is dictated by their binding to different activators as in mitotic cells.…”
Section: Introductionmentioning
confidence: 99%